2018
DOI: 10.1007/s00394-018-1788-9
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of gut Prevotella at baseline and metabolic response to barley prebiotics

Abstract: NCT02427555.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The baseline levels of Prevotella and Bacteroides were not predictive of the metabolic response. Furthermore, the subjects with a high ratio of Prevotella/Bacteroides displayed a lower insulin response compared to the subjects with a low ratio, independent of the intervention [31]. A similar study was conducted by Kovatcheva-Datchary et al, where the intake of barley kernel bread was compared with white wheat bread in 39 healthy participants in a short-term crossover study [32].…”
Section: Healthy Normal-weight Individualsmentioning
confidence: 76%
See 2 more Smart Citations
“…The baseline levels of Prevotella and Bacteroides were not predictive of the metabolic response. Furthermore, the subjects with a high ratio of Prevotella/Bacteroides displayed a lower insulin response compared to the subjects with a low ratio, independent of the intervention [31]. A similar study was conducted by Kovatcheva-Datchary et al, where the intake of barley kernel bread was compared with white wheat bread in 39 healthy participants in a short-term crossover study [32].…”
Section: Healthy Normal-weight Individualsmentioning
confidence: 76%
“…A plant-based diet rich in fiber has recently been linked to a Prevotella enterotype, whereas the Bacterioides enterotype was associated with a high intake of protein and fat [53,54]. In the study by Sandberg et al the Prevotella/Bacteroides ratio at baseline was not predictive of the metabolic response to grain intervention [31]. This was, with the exception of some participants, also the finding after intake of whole-grain in the study by Schuttle et al [39].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Prevotella copri and Enterococcus faecalis play significant roles in the metabolism of aspirin (Fig 6). The abundance of the Prevotella/Bacteroides may be beneficial for metabolism [9]. This may explain that the metabolic activity of aspirin in the high-altitude environment is inhibited.…”
Section: Plos Onementioning
confidence: 99%
“…Yet another short-term study (3 days) conducted with barley kernel bread showed that individuals who had higher Prevotella abundance responded to the dietary treatment and had improved glucose metabolism [30]. In a follow-up study it was defined that not the abundance of Prevotella per se but the Prevotella/Bacteroides ratio was the parameter capable of stratifying metabolic responders [73]. Furthermore, Prevotella has also been associated inversely with clinical parameters of obesity related low-grade inflammation, including lipopolysaccharide and high-sensitive C-reactive Protein (hs-CRP), as was reviewed recently [74].…”
Section: The Gut Microbiota As a Predictor Of Responsiveness To A Heamentioning
confidence: 99%